Characterization and the hermeneutics of recognition in Virginia Woolf's The Voyage Out. Issue 2 (4th May 2022) - Dikova, Stanislava
ABSTRACT: This article traces Virginia Woolf's interest in the representation of women back to her first published novel, The Voyage Out (1915). It argues that her dissatisfaction with traditional modes of women's characterization stems from their reliance on recognizable patriarchal models of personhood, an unhealthy dependence which restricts the development of new forms of gendered political and personal identification. This reading uses the concept of recognition, as understood in the post-Hegelian feminist tradition, as a key structuring and interpretative tool to demonstrate Woolf's early critical insight into the fraught relationship between idealized narratives of individual autonomy and gender. In doing so, it makes a case for the broader inclusion of recognition as a critical term of inquiry in modernist studies, both as an aesthetic and political site of contention.